Convergence analysis of massive mimo antenna arrays using a Geometry-based stochastic channel model - DANUOR,Patrick (KNUST, 2025)
A thesis submitted to theDepartment of telecommunications engineering College of engineering In partial fulfillment of the requirements for the degree ofMPhil. Telecommunications engineering